Analisis Keruangan Sektor Ekonomi Unggulan di Kabupaten Ponorogo Tahun 2011-2014 - Miftakul Janah, Siti, Drs. M. Musiyam, M.TP, Drs. Priyono, M.Si (2017)
This research aims to identify and analyze the potential sectors, the competitive superiority and the specialization of the existing sectors as well as the area spatial condition in all Sub districts in Ponorogo Regency in period of 2011-2014 that will be used for developing the development in Ponorogo Regency, generally in each Sub district, especially in order to implement the regional autonomy. The data used in this research are secondary data consisting of data on the Gross Regional Domestic Product (PDRB) of Ponorogo Regency and Per-Sub district in Ponorogo Regency in 2011-2014 obtained at the Office of Statistics Central Bureau of Ponorogo Regency, Department of Public Works of Ponorogo Regency and Regional Development Planning Agency (Bappeda) of Ponorogo Regency. Analysis used is the analysis of Location Quotient, Shift Share and uses Geographical Information System (SIG). The results of Locationt Quotient analysis concluded that each Sub district has their own potential sector in accordance with the their area condition. Most of Sub districts (17) have basic sectors of agricultural sector, trade sector, hotel and restaurant, financial sector, and rental and service. Nevertheless, those that have the basic sector of construction and service was only one Sub district. The results of the Shifth Share analysis showed that all economic sectors in each sub district are competitive sectors, except the mining sector in Sooko Sub district which is not a competitive sector. From the results of the LQ and Shift Share analysis, it can be determined that the superior potential sectors are the agricultural sector and financial sector, the rental and service in 15 Sub districts; the mining sector in 4 Sub districts; the industrial sector in 5 sub districts; the construction sector and the service sector in one Sub district; the trade sector, hotel and restaurant in 17 Sub districts; the transportation and communication sector in 2 Sub districts; and the Electricity, gas, and water sector which is not superior in all Sub districts in Ponorogo regency. Keywords: Superior Sector, Location Quetient, Shift Share, and Geographical Information System.